KONSEP WALKABILITY INDEX DAN PENANGANAN FASILITAS PEJALAN KAKI PADA KAWASAN JALAN PERKOTAAN DI INDONESIA - Erlangga, Dwiky; Handayani, Dewi; Syafi'i, Syafi'i (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2020)
Walkability Index (WI) is a method to assess the walkability level on pedestrian facilities with the main components of: safety and security, convinience and attractiveness, as well as government policies. Generally, this method is utilized to review the pedestrian facilities walkability in urban areas, particularly in CBD (Central Business District) which is the hub for activities center, such as economic, business, education, healthcare, transit to tourism areas. The rapid development of activities leads to the increasing number of visitors in those areas, such as on Jalan Slamet Riyadi, Surakarta. This condition needs to be balanced with the availability of adequate facilities and infrastructure, one of them is the sidewalks to facilitate the pedestrian movement from one place to another. Indonesia did not have any assessment criteria for sidewalks in terms of scoring even though some variables on WI have already existed in the Circular Letter of the Minister of Public Works and Public Housing 02/SE/M/2018 on the Guidelines for Pedestrian Facility Planning. This paper presents the recommendation of assesment and category based on the regulation in Indonesia. It is expected to benefit the determination of priority on pedestrian facility handling in the field. Literature study as the foundation of this paper attempts to accomodate the pedestrian facility variables contained in the regulation of Indonesia using the scoring method with several recommendations in the category of handling, with the basis of WI analysis method. The results of the analysis show that there are 3 variables that need to be considered more in the planning criteria for sidewalk in Indonesia that affect the determination of handling recommendation including the supporting and additional facilities, facilities for disabled pedestrians, and the needs of wide space for pedestrians.